Utilization of kootu among women microentrepreneurs - Zainal Abidin, Faudziah (2005)
This study analysis the role of kootu to women micro-entrepreneurs. In-depth interviews with women micro-entrepreneurs revealed three main functions of kootu: as a form of financial management, as a channel for mobilizing savings, and for capital formation. These functions help mediate the roles some women face as business owners and heads of households for their families. It demonstrates womens experience as borrowers and lenders of money, their willingness to take risks as well as their ability to use credit for productive uses. It also exhibits womens attempts at improving their families standard of living. The prevalent use of kootu also helps explain why it has remained particularly popular among low-income women. In some cases, it has become the primary method of gaining access to credit. The organization of kootu and its procedures may serve valuable: to formal lenders in developing products or services to meet women (credit needs).